Characterization of transgenic Trifolium subterraneum L. which expresses phyA and releases extracellular phytase: growth and P nutrition in laboratory media and soil - GEORGE, T. S.; RICHARDSON, A. E.; HADOBAS, P. A.; SIMPSON, R. J. (Plant, cell and environment, 2004)
ABSTRACT Transgenic Trifolium subterraneum expressing a phytase gene (phyA) from Aspergillus niger were generated. Five independently transformed lines showed an average 77‐fold increase in exuded phytase activity in comparison with null segregant and wild‐type controls. Unlike other phosphatases, exuded phytase activity was unaffected by P supply, verifying the constitutive expression of phyA. Transgenic T. subterraneum grown in agar with P supplied as phytate, took up 1.3‐ to 3.6‐fold more P than controls and had equivalent P uptake to plants supplied with orthophosphate. This unique phenotype was compromised when the plants were grown in soil. None of the five lines showed increased shoot biomass or total P uptake in an unfertilized, low‐P soil taken from under permanent pasture. With addition of P, one of the five transgenic lines had consistently greater P nutrition compared with control plants. Despite variable growth and P nutrition responses, P uptake per root length was on average greater for transgenic lines. Exudation of phytase by transgenic T. subterraneum allowed utilization of P from phytate in non‐sorbing, sterile laboratory media, but was less effective when plants were grown in soil. Release of extracellular phytase is therefore not the only requirement for the acquisition of P from endogenous soil phytate by plants.